Profiles of Plasmodium falciparum infections detected by microscopy through the first year of life in Kintampo a high transmission area of Ghana - Botwe, Akua Kyerewaa; Owusu-Agyei, Seth; Asghar, Muhammad; Hammar, Ulf; Oppong, Felix Boakye; Gyaase, Stephaney; Dosoo, David; Jakpa, Gabriel; Boamah, Ellen; Twumasi, Mieks Frenken; Osier, Faith; Färnert, Anna; et al. (PLOS ONE, 2020)
Although malaria mortality among children under five years of age is high, the characteristics of their infection patterns are not well described. The aim of this study was to examine the longitudinal sequence pattern of Plasmodium falciparum infections in the first year of life within a birth cohort in Kintampo, Ghana (N = 1855). Infants were monitored at home with monthly sampling and also at the clinic for any febrile illness between 2008 and 2011. Light microscopy was performed on monthly scheduled visits and febrile ill visits over twelve months of follow-ups (n = 19231). Microscopy-positive visits accompanied with or without symptoms were rare during the first five months of life but were common from six to twelve months of age. Among 1264 infants with microscopy data over a minimum of eight monthly visits and also throughout in sick visits, some were microscopy negative (36%), and others positive: only-symptomatic (35%), alternating (22%) and only-asymptomatic (7%). The median age of microscopic infection was seven months for the alternating group and eight months for both the only-symptomatic and only-asymptomatic groups. The alternating group had the highest cumulative incidence of microscopic infections, the lowest age at first infection and 87 different infection patterns. Parasite densities detected by microscopy were significantly higher for symptomatic versus asymptomatic infection. We conclude that infants in malaria endemic areas experience diverse infection profiles throughout their first year of life. Further investigations should include submicroscopic reservoir and may shed more light on the factors that determine susceptibility to malaria during infancy.
Gesehen am 03.05.2021